(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2017)
Modern technologies for the construction of a subway underground allow reconstruction of operated stations without stopping the movement of trains and subway disruptions. However, this problem is quite complicated, because at the device of transitive tunnels it is possible to violate the stress-strain state of the main load-bearing structures and ground of the station base, track upper-structure drawdown appearance that is impermissible for the safe operation of the subway. The article presents the results of the preparatory stage of theMinsk subway station main load-carrying structures state monitoring, as well as the results of spatial calculations based on design data, considering the stage of transition tunnel construction work from the first to the third branches.